Proyeksi Kinerja PT Kimia Farma Tbk. Berdasarkan Tren Rasio Keuangan 2023-2024 - Eka Septia Haryanti; Ema Ratna Sari; M. Thoha Ainun Najib (P3M Politeknik Negeri Bengkalis, 2025)
This study aims to analyze the trend of PT Kimia Farma Tbk. financial ratios, including liquidity, solvency, activity, and profitability ratios in the 2023-2024 period, and to project its future financial performance. A descriptive quantitative approach is used by analyzing secondary data from the audited annual financial statements of PT Kimia Farma Tbk. The scope of the study is limited to evaluating the four categories of financial ratios. The results of the analysis show that PT Kimia Farma Tbk. has very strong liquidity, far exceeding the industry average, which is its only significant strength. However, the company faces serious weaknesses in the solvency aspect, marked by high debt levels and very low interest payment capabilities in 2024. Operational efficiency in the activity ratio is also low, reflected in the turnover of receivables, inventory, and fixed assets which are far below industry standards. At its peak, PT Kimia Farma Tbk. profitability is very poor, shifting from a thin margin in 2023 to a net loss in 2024. In conclusion, although PT Kimia Farma Tbk. liquidity is solid, the prospects for future performance are very worrying due to deep solvency, activity, and profitability problems. Without drastic strategic changes, such as increased operational efficiency, margin improvement, debt restructuring, or capital injection, the company's sustainability will be threatened.